Prevention of Wrong-Way Driving on Freeways - Topolšek, Darja (Promet - Traffic&Transportation, 2007)
Traffic accidents that occur on freeways often end tragicallybecause of high driving speed. Wrong-way driving is also one ofthe causes of accidents on freeways. Research is based on theanalysis of traffic accident data caused by wrong-way drivingon freeways, and considering valid technical specifications forconnections and junctions design elements. Research is basedon the analysis of the data of traffic accidents that occurred becauseof wrong-way driving on freeways and on the considerationof valid technical specifications concerning connectionsand junction design elements. The thesis presents possiblecountermeasures for prevention of wrong-way driving and consequentialdecrease in the number of traffic accidents. The proposedprevention countermeasures of wrong-way driving onfreeways could greatly reduce incorrect traffic vehicle movementsthat are the consequence of wrong-way driving and thuspositively enhance the traffic safety level on freeways.